2009
DOI: 10.1364/oe.17.004061
|View full text |Cite
|
Sign up to set email alerts
|

Retinal blood flow detection in diabetic patients by Doppler Fourier domain optical coherence tomography

Abstract: We present human retinal blood flow investigation for diabetic patients using Doppler Fourier domain optical coherence tomography (FD-OCT). The scanning pattern consisted of two concentric circles around the optic nerve head. The blood flow in one patient with diabetes and no retinpathy and another patient with treated proliferative diabetic retinopathy were measured. The patient without retinopathy showed a total blood flow value at the lower level of the normal range. The flow distribution between superior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 35 publications
3
73
1
1
Order By: Relevance
“…13,14 Doppler OCT measurements made with the newer semi-automated DOCTORC software agreed closely with the results of manual measurements that we published previously. [1][2][3][4][5] The difference between DOCTORC measurements and manual measurements in individual cases, as measured by CV, is similar to inter-grader differences. This indicates that the difference was primarily associated with subjective portion of the grading process, and not the difference between software.…”
Section: -5supporting
confidence: 52%
See 1 more Smart Citation
“…13,14 Doppler OCT measurements made with the newer semi-automated DOCTORC software agreed closely with the results of manual measurements that we published previously. [1][2][3][4][5] The difference between DOCTORC measurements and manual measurements in individual cases, as measured by CV, is similar to inter-grader differences. This indicates that the difference was primarily associated with subjective portion of the grading process, and not the difference between software.…”
Section: -5supporting
confidence: 52%
“…[6][7][8][9][10] Volumetric measurement of retinal blood flow gives valuable information about the disease process. [4][5][6]11,12 DOCTORC provides a practical way to estimate total retinal blood flow based on the measurements in individual vessels determined by Doppler OCT using the double circle scan pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic dysfunction increased by high glucose level and other signalling pathways activation leads to DR progression. At present, DR represented by glycemic control which is the most effective medical treatment (Hudson, 1996;Aiello, 2003;Porta and Allione, 2004;Wang et al, 2009). There are Studies which showed that blood sugar level control is more important (Schaumberg et al, 2005;Kilpatrick et al, 2006).…”
Section: Proliferative Retinopathy (Pdr)mentioning
confidence: 99%
“…Since the real eye optical system is complex, 18,19 factors such as multiple refracting surfaces from the cornea and ocular lens, among others, complicate the blood flow rate calculation. As a preliminary study, we employed a simplified optical model of the eye as used by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…As a preliminary study, we employed a simplified optical model of the eye as used by other groups. 11,13,18 We simplified the multiple refracting ocular surfaces into a single ocular lens, and assumed the single ocular lens can focus a collimated beam perfectly onto the retina. We also assumed that the simplified ocular lens would not modify the preset incident angles.…”
Section: Introductionmentioning
confidence: 99%